Constitutional principles of functioning of democratic institutions in the conditions of COVID-19 pandemic: Domestic practice and foreign experience - Batanov, Oleksander; Batanova, Nataliya; Verlos, Natalia; Omelchenko, Nataliya; Lukashenko, Alyona (DIXI, 2021)
Due to the spread of the coronavirus infection around the world, there is a threat of destabilization of the democratic development of most countries. Therefore, the objective reality of today is the need for global consolidation of states and the advance of a promising strategy for the development of democracy in the context of the covid-19 pandemic. As a result of the study, the authors suggest that to overcome the crisis in the post-war period, democracies should also take several measures, including: to adopt a “Global Declaration of Human Rights in a Pandemic”, as well as the conditions and possibilities of their limitation; to carry out the reception of the norms proclaimed in the proposed declaration by national Constitutions; to promote the dissemination of information of a legal and educational nature, aimed at the formation of global legal awareness to develop a person’s ability to self-limit guaranteed constitutional rights in the event of a pandemic; to improve the constitutionalization of digital human rights to overcome digital discrimination and create an effective system to guarantee and protect digital rights.
Keywords: covid-19 pandemic; constitutional human rights; constitutionalism; constitutionalization of digital human rights; democracy; restrictions on constitutional human rights